Evaluating Biosimilar Development Projects: An Analytical Framework Utilizing Net Present Value - Ranbhor R; Kulkarni P (Biologics: Targets & Therapy)
Ranjit Ranbhor,1 Priyanka Kulkarni2 1Pergament and Cepeda LLC, Florham Park, NJ, 07932, USA; 2Feliciano School of Business, Montclair State University, Montclair, NJ, 07043, USACorrespondence: Ranjit Ranbhor, Email ranjitranbhor@gmail.comBackground: The increasing prominence of biosimilars in healthcare delivery has created the need for robust financial evaluation methods to assess development opportunities. Unlike traditional generic drugs, biosimilars require substantial investments ($100-250 million) and longer development timelines (6– 8 years), necessitating sophisticated evaluation approaches.Methods: This study presents a comprehensive Net Present Value (NPV) analysis framework specifically designed for biosimilar development projects. Our framework incorporates key technical, regulatory, and commercial factors through a risk-adjusted NPV methodology, validated through case studies of three monoclonal antibody biosimilar development programs.Results: The analysis reveals that successful projects require minimum peak sales of $250-300 million to achieve a positive NPV, with market share and manufacturing efficiency serving as critical value drivers. Cost analysis shows that clinical development represents the largest share (57%) of total development costs.Conclusion: The framework demonstrates that early market entry, manufacturing optimization, and market share achievement are key success factors, whereas technical complexity and competitive intensity significantly influence risk-adjusted returns.Keywords: biosimilars, net present value analysis, investment evaluation, pharmaceutical development, risk assessment